2020
DOI: 10.3174/ajnr.a6829
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Developmental Venous Anomalies: Clinicoradiologic Characterization and Follow-Up

Abstract: BACKGROUND AND PURPOSE: Although developmental venous anomalies have been frequently studied in adults and occasionally in children, data regarding these entities are scarce in neonates. We aimed to characterize clinical and neuroimaging features of neonatal developmental venous anomalies and to evaluate any association between MR imaging abnormalities in their drainage territory and corresponding angioarchitectural features. MATERIALS AND METHODS: We reviewed parenchymal abnormalities and angioarchitectural f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It should be noted that parenchymal or ventricular abnormalities were present in 36.6% with improvement over time and normal neurologic outcome in 64.2% of those with a clinical follow-up. 17 Our study has a few limitations. Since frontal horns are not routinely visualized completely on survey images, it is conceivable that smaller volumes of echogenic material may be overlooked and diagnosed as normal.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It should be noted that parenchymal or ventricular abnormalities were present in 36.6% with improvement over time and normal neurologic outcome in 64.2% of those with a clinical follow-up. 17 Our study has a few limitations. Since frontal horns are not routinely visualized completely on survey images, it is conceivable that smaller volumes of echogenic material may be overlooked and diagnosed as normal.…”
Section: Discussionmentioning
confidence: 93%
“…A study of 41 newborns demonstrated the presence of DVAs in 1.9% with retrospective confirmation of a congenital origin in one‐quarter of the cases with fetal MRI imaging. It should be noted that parenchymal or ventricular abnormalities were present in 36.6% with improvement over time and normal neurologic outcome in 64.2% of those with a clinical follow‐up 17 …”
Section: Discussionmentioning
confidence: 97%
“…In particular, VGAM is characterized by an arteriovenous shunting of the arterial limbic system (e.g., choroidal and pericallosal arteries) draining into the vein of Galen forerunner (2). Neonatal presentation of the deriving aneurysmal formation is usually associated with high-output heart failure (3), and later high mortality and morbidity rates, such as seizures and neurodevelopmental impairment, despite the advances in prenatal diagnosis and postnatal embolization procedures (4)(5)(6)(7). Furthermore, an accurate neurophysiological and neuroimaging assessment could be useful in predicting the prognosis and improving short-and long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%